[PP.16.17] DO MODERATE TO HIGH CARDIOVASCULAR RISK PATIENTS ACCURATELY PERCEIVE THEIR OWN VASCULAR AGE?. (September 2016) - Bergerot, C.; Giaconia, M.B.; Lamoureux, S.; Schaaf, M.; Mewton, N.; Ovize, M.
Abstract : Objective: Estimation of vascular age (VA) derived from the Framingham risk equations has been proposed as a useful tool to improve adherence and compliance of hypertensive patients. In the general field of cardiovascular prevention (CVP), little is known on the patient's understanding of his own VA as compared to legal age (vascular age difference = VAD). We sought to evaluate association between qualitative self-evaluation by patients for their VA and patient's characteristics and calculated VAD by the Framingham risk equations. Figure. No caption available. Design and method: Patients admitted in CV outpatient clinic for either primary or secondary CV prevention were asked to give an estimation of their own VA on a qualitative scale. Patients were then categorized in 2 groups: younger or same age (group 1) or older than legal age (group 2). The 2 groups were then compared in terms of basic characteristics and for calculated VAD. Results: Among 99 consecutive patients (age 62 ± 12, 78% males, 53% primary prevention), eleven patients couldn't give any estimation. 52 patients (53%) were categorized in group 1. There was no significant difference in between groups for VAD and baseline characteristics. However, patients of group 2 were younger, had more myocardial infarction history and were more likely smokers (table) Conclusions: Self-estimation of vascular aging by patients was not associated with calculated vascular aging, suggesting that moderate to high risk patients still misbelieve on their own risk. However, a younger age, smoking status and past history of cardiovascular disease seem to influence patient for perceiving their arteries to be older.